Development of Media Block Training Volleyball - Eka Supriatna; Rubiyatno Rubiyatno (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to develop a volleyball block training tool media. Based on observations made in volleyball clubs throughout the city of Pontianak, there is no volleyball block training tool media, so it is necessary to develop a volleyball block training media. This development uses the R&B development model with the ADDIE development model. Meanwhile, the data analysis technique, namely the percentage, was adopted from Sudjana (2016). The results of the development of the volleyball block training tool media meet the criteria that are quite valid for media experts to get a score of 85.2% in the Very Eligible category, Material experts get a score of 89.6% meet the Very Eligible criteria, and the assessment for small group trials gets a score of 78.5 %,  while the large group trial obtained a score of 80.1%. The conclusion of this study is that the development of volleyball block training media is very feasible to be used as a volleyball block technique training medium.